Sensorless control of switched reluctance motor based on inductance characteristic point under magnetic saturation - Hui Cai; Yuhua Fan (Scientific Reports)
Abstract This paper presents a method of rotor position estimation for switched reluctance motors suitable for saturation. The effects of saturation as well as voltage changes are taken into account at the same time. It is based on the inductance in the unsaturated region. When the phase inductance is equal to the threshold, it is defined as a characteristic point. Meanwhile the characteristic pulse signal is triggered. Different inductance intersection thresholds are determined when the phase current and bus voltage change. The rotor position is estimated by interval speed. Compared with the traditional inductance method, the position estimation error is smaller. Finally, the correctness and effectiveness of the proposed method are verified by simulation and experiments.